Association of Excess Dietary Iodine Intake with Papillary Thyroid Carcinoma - Roy, Sutanu; Sultana, Sadia; Azam, Md Nurul; Salma, Umme (Bangladesh Journal of Nuclear Medicine, 2023)
Background: Papillary thyroid carcinoma (PTC) is the most common type of differentiated thyroid carcinoma and accounts for 70–80% of all thyroid carcinomas. After the global iodine fortification of salt and food, the incidence of PTC has been increasing throughout the world in recent years. Aims: To determine the relationship between excessive dietary iodine intake and PTC. Patients and methods: This cross-sectional study was carried out at the National Institute of Nuclear Medicine & Allied Sciences (NINMAS), Dhaka, from March 2020 to June 2021. A total of 111 patients were included in this study, of whom 53 were pre-operative papillary thyroid carcinoma patients and the rest, 58, were age- and sex-matched healthy individuals. Their urinary iodine concentrations were measured in the laboratory of the Bangladesh Reference Institute for Chemical Measurements (BRICM). Urinary iodine concentration is a good marker of dietary iodine intake. Statistical analysis of the results was obtained using Windows-based computer software devised with Statistical Packages for Social Sciences (SPSS) version 23.0. Results: The mean urinary iodine concentration was 223.54±55.78 microgram/liter in the PTC group and 154.29±61.83 microgram/liter in the healthy group. A remarkable number of participants in both the PTC group 42 out of 53 (79.3%) and the healthy group 18 out of 58 (31.0%) had biochemical evidence of excess iodine intake. Excess iodine intake significantly (p<0.05) increased with 8.48 times odds (95% CI 3.30-22.33) in PTC patients. Conclusion: This study revealed that a significant number of participants in the PTC group had evidence of excess iodine intake compared to that of the healthy group, which suggests that excess dietary iodine intake may be related to the occurrence of PTC. Bangladesh J. Nuclear Med. 26(1): 25-30, 2023